Synthesis of Spirocyclic 1‐Pyrrolines from Nitrones and Arynes through a Dearomative [3,3′]‐Sigmatropic Rearrangement - Alshreimi, Abdullah S.; Zhang, Guanqun; Reidl, Tyler W.; Peña, Ricardo L.; Koto, Nicholas‐George; Islam, Shahidul M.; Wink, Donald J.; Anderson, Laura L. (Angewandte Chemie International Edition, 2020)
A dearomative [3,3′]‐sigmatropic rearrangement that converts N‐alkenylbenzisoxazolines into spirocyclic pyrroline cyclohexadienones has been developed by using the dipolar cycloaddition of an N‐alkenylnitrone and an aryne to access these unusual transient rearrangement precursors. This cascade reaction affords spirocyclic pyrrolines that are inaccessible through dipolar cycloadditions of exocyclic cyclohexenones and provides a fundamentally new approach to novel spirocyclic pyrroline and pyrrolidine motifs that are common scaffolds in biologically‐active molecules. Diastereoselective functionalization processes have also been explored to demonstrate the divergent synthetic utility of the unsaturated spirocyclic products. A cascade reaction has been designed for the synthesis of spirocyclic pyrrolines from nitrones and arynes. A key feature of this transformation is an unusual dearomative [3,3′]‐sigmatropic rearrangement of a heterocyclic intermediate that results in a spirocyclization. This modular approach provides access to three‐dimensionally‐defined pyrrolines and pyrrolidines with opportunities for divergent derivatization.